2017
DOI: 10.1016/j.ajpath.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

The Increased Transforming Growth Factor-β Signaling Induced by Diabetes Protects Retinal Vessels

Abstract: The roles of transforming growth factor (TGF)-b in extracellular matrix production and vascular remodeling, coupled with increased TGF-b expression and signaling in diabetes, suggest TGF-b as an important contributor to the microangiopathy of diabetic retinopathy and nephropathy. To investigate whether increased TGF-b signaling could be a therapeutic target for preventing retinopathy, we used a pharmacologic approach (SM16, a selective inhibitor of the type 1 TGF-b receptor activin receptorelike kinase 5, oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
(57 reference statements)
0
17
0
Order By: Relevance
“…Controversy still exists regarding the role of the TGF-β family members in choroidal neovascularization (CNV), since they have a pleiotropic effect and may play different roles in the regulation of vascular endothelial and smooth muscle cells, being either anti- or pro-angiogenic in a context-dependent way 4 , 5 . In the eye, TGF-β has been shown to act as an anti-angiogenic factor 6 and to protect retinal pigment epithelium (RPE) cells and retinal vasculature 7 10 . However, other findings suggest it has a pro-angiogenic effect in the eye: TGF-β not only induces VEGF-A expression by RPE 11 , but its direct and indirect inhibition has also been linked to the inhibition of both the epithelial-mesenchymal transition and senescence of RPE cells in vitro 12 15 , as well as to the blockage of CNV 16 – 18 , including the subretinal fibrosis stage 19 , 20 , in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Controversy still exists regarding the role of the TGF-β family members in choroidal neovascularization (CNV), since they have a pleiotropic effect and may play different roles in the regulation of vascular endothelial and smooth muscle cells, being either anti- or pro-angiogenic in a context-dependent way 4 , 5 . In the eye, TGF-β has been shown to act as an anti-angiogenic factor 6 and to protect retinal pigment epithelium (RPE) cells and retinal vasculature 7 10 . However, other findings suggest it has a pro-angiogenic effect in the eye: TGF-β not only induces VEGF-A expression by RPE 11 , but its direct and indirect inhibition has also been linked to the inhibition of both the epithelial-mesenchymal transition and senescence of RPE cells in vitro 12 15 , as well as to the blockage of CNV 16 – 18 , including the subretinal fibrosis stage 19 , 20 , in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, intracellular angiotensin II signaling has recently been shown to be upregulated in cardiac fibroblasts derived from a canine model of congestive heart failure, and intracellular, but not extracellular, angiotensin II increases collagen‐1 gene expression and collagen secretion in cardiac fibroblasts, again pointing to the importance of intracellular blockade. The potential need for noncanonical intracellular blockade is suggested by the inability of intracellular AT1R blockade to inhibit all intracellular angiotensin II actions . Potentially useful therapeutic approaches in systolic heart failure, chronic renal disease, and AMD include the use of extracellular and intracellular inhibitors of the RAS and TGF‐β as well as mineralocorticoid receptor antagonists and possibly inhibitors of Wnt/β‐catenin signaling .…”
Section: Discussionmentioning
confidence: 99%
“…The potential need for noncanonical intracellular blockade is suggested by the inability of intracellular AT1R blockade to inhibit all intracellular angiotensin II actions . Potentially useful therapeutic approaches in systolic heart failure, chronic renal disease, and AMD include the use of extracellular and intracellular inhibitors of the RAS and TGF‐β as well as mineralocorticoid receptor antagonists and possibly inhibitors of Wnt/β‐catenin signaling . It should be noted, however, that evidence exists to suggest that some elevation of TGF‐β in diseases such as diabetic retinopathy, as opposed to diabetic nephropathy, may actually be protective by supporting vasculature integrity, indicating that more work needs to be done to determine the appropriate degree and duration of positive loop inhibition in various disorders and tissues; whether any such protective action depends on intracellular, as opposed to canonical extracellular, TGF‐β action should also be determined because blocking 1 (intracellular action, for example) but not another mode of action (conical extracellular signaling) could inhibit pathogenic feedforward loops while maintaining any protective action .…”
Section: Discussionmentioning
confidence: 99%
“…In recent times, isoforms of TGF have been studied closely for its downstream effects on certain microRNA (miRNAs) species [202]. It has also been reported that extreme glucose levels may possibly upsurge transcription of TGF-β genes which in turn promotes the elevation levels of TGF-β and its downstream signalling [203][204][205]. Although the mode by which TGF-β activation causes heart problems in diabetic subjects is vague, its activation in such subjects could result from the modulation of the expression of certain changes in miRNAs.…”
Section: 2mentioning
confidence: 99%